Abdominal obesity in Japanese-Brazilians: which measure is best for predicting all-cause and cardiovascular mortality? Obesidade abdominal em nipo-brasileiros: que medida antropométrica tem maior capacidade de predizer a mortalidade geral e por doenças cardiovasculares? - Marselle Rodrigues Bevilacqua; Suely Godoy Agostinho Gimeno (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
This study aimed to verify which anthropometric measure of abdominal obesity was the best predictor of all-cause and cardiovascular mortality in Japanese-Brazilians. The study followed 1,581 subjects for 14 years. Socio-demographic, lifestyle, metabolic, and anthropometric data were collected. The dependent variable was vital status (alive or dead) at the end of the study, and the independent variable was presence of abdominal obesity according to different baseline measures. The mortality rate was estimated, and Poisson regression was used to obtain mortality rate ratios with abdominal obesity, adjusted simultaneously for the other variables. The mortality rate was 10.68/thousand person-years. Male gender, age > 60 years, and arterial hypertension were independent risk factors for mortality. The results indicate that prevalence of abdominal obesity was high among Japanese-Brazilians, and that waist/hip ratio was the measure with the greatest capacity to predict mortality (especially cardiovascular mortality) in this group. O objetivo foi verificar qual medida antropométrica de obesidade abdominal melhor prediz mortalidade geral e por doenças cardiovasculares entre nipo-brasileiros. Foram seguidos, por 14 anos, 1.581 sujeitos. Coletaram-se dados sociodemográficos, de estilo de vida, metablicos e antropométricos. Considerou-se vivo ou óbito ao final do estudo como variável dependente e a presença de obesidade abdominal por diferentes medidas na linha de base como variável independente. Estimou-se o coeficiente de mortalidade e se usou o modelo de Poisson para obtenção das razões entre eles e a obesidade abdominal, ajustados simultaneamente às demais variáveis. O coeficiente de mortalidade foi de 10,68/mil pessoas-ano. O gênero masculino, a idade > 60 anos e ter hipertensão arterial foram fatores de risco independentes para mortalidade. Os resultados indicaram que entre nipo-brasileiros a prevalência de obesidade abdominal foi elevada e que a razão cintura quadril foi a medida que apresentou maior capacidade de predizer a mortalidade, especialmente cardiovascular, entre tais indivíduos.